Chemotherapy-induced peripheral neuropathies: an integrative review of the literature - Talita Cassanta Costa; Miriam Lopes; Anna Cláudia Yokoyama dos Anjos; Marcia Maria Fontão Zago (SciELO, 2015)
OBJECTIVE: To identify scientific studies and to deepen the knowledge of peripheral neuropathies induced by chemotherapy antineoplastic, seeking evidence for assistance to cancer patients. METHOD: Integrative review of the literature conducted in the databases Latin American and Caribbean Health Sciences (LILACS), Scientific Electronic Library Online (SciELO), Medical Literature Analysis (PubMed/MEDLINE), the Cochrane Library and the Spanish Bibliographic Index Health Sciences (IBECS). RESULTS: The sample consisted of 15 studies published between 2005-2014 that met the inclusion criteria. Studies showed aspects related to advanced age, main symptoms of neuropathy and chemotherapy agents as important adverse effect of neuropathy. CONCLUSION: We identified a small number of studies that addressed the topic, as well as low production of evidence related to interventions with positive results. It is considered important to develop new studies proposed for the prevention and/or treatment, enabling adjustment of the patient's cancer chemotherapy and consequently better service.